2018
DOI: 10.18016/ksutarimdoga.vi.472890
|View full text |Cite
|
Sign up to set email alerts
|

Tarımda Kalma Eğilimini Etkileyen Başlıca Faktörlerin Genel Bir Değerlendirmesi

Abstract: The agriculture sector always maintains its importance in all countries mainly due to its economic contributions to the components such as employment, export, investment, raw material creation and creation of value added, especially in meeting the food needs of the society. Also, agricultural sector in Turkey continues its importance in all matters referred predominantly. However, at this point, despite the importance, there is a aging producer problem in agriculture causing them moving away from agriculture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…The results obtained from this study also support other studies previously conducted on this topic. Sav and Sayın (2018) stated that long-term policies were needed for agriculture; agriculture in Turkey was steadily aging, and some of its important problems were its structure of small and fragmented land areas, inadequacy of producer organization, increase in input prices and a low education level. Doğan et al (2015) and Yıldız et al (2017) drew attention to a similar situation and it was reported in the study by Yıldız et al (2017) that 93% of the farmers participating in the study saw increase in the cost of inputs as the most important problem.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from this study also support other studies previously conducted on this topic. Sav and Sayın (2018) stated that long-term policies were needed for agriculture; agriculture in Turkey was steadily aging, and some of its important problems were its structure of small and fragmented land areas, inadequacy of producer organization, increase in input prices and a low education level. Doğan et al (2015) and Yıldız et al (2017) drew attention to a similar situation and it was reported in the study by Yıldız et al (2017) that 93% of the farmers participating in the study saw increase in the cost of inputs as the most important problem.…”
Section: Resultsmentioning
confidence: 99%
“…2000 yılından sonra doğrudan ödeme yoluyla verilen destekleme tutarlarının iyi olması, üreticilerin tarımsal faaliyetlerini sürdürmesini olumlu etkileyen faktörlerin başında gelmiştir. Ancak doğrudan desteklemelerin nakit olarak yapılması üreticilerin desteklemelere bağımlı kalmasına yol açmıştır [21].…”
Section: Uşak İlinin Tarımsal Destekleme Ve Projeler Durumuunclassified
“…Organik ürünlerdeki fiyat yüksekliği avantajı, önemli miktarda organik tarım ürünü kullanıma sunulduğunda ortadan kalkacağı için pek yardımcı olmayacaktır (Narayanan, 2005). Devlet desteklerinin yetersiz oluşu çiftçilerin konvansiyonel tarımdan organik tarıma geçişi üzerinde negatif bir etki yaratmaktadır (Bozyiğit ve Kılınç Doğan, 2015;Erem Kaya ve Atsan, 2013;Karabaş, 2011;Kızılaslan ve Taner, 2011;Sav ve Sayın, 2018;Yener,2017).…”
Section: Introductionunclassified